ECONOMIC EFFICIENCY AND ANTHROPOGENIC RISKS OF REGENERATION OF INDUSTRIAL OILS - Ranskiy, Anatoliy; Gordienko, Olga; Titov, Taras; Tkachenko, Stanislav; Pivovarov, Aleksandr (Proceedings of National Aviation University (archive), 2014)
In this article a principal scheme of a modification of the regenerated industrial oil by additives derived by reagent recycling of the obsolete pesticides and shown the decrease in anthropogenic risks of their reagent processing was developed. The economic effect of usage of the studied additives in the regenerated industrial oils was calculated.